Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Daijun Liu; Franz Essl; Bernd Lenzner; Dietmar Moser; Philipp Semenchuk; Tim M. Blackburn; Phillip Cassey; Dino Biancolini; César Capinha; Wayne Dawson; Ellie E. Dyer; Benoit Guénard; et al. (Global Change Biology, 2024)
The ecological impact of non‐native species arises from their establishment in local assemblages. However, the rates of non‐native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non‐native species and residence of non‐native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non‐native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non‐native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi‐natural ecosystems. Notably, non‐native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land‐use types rather than croplands and urban areas. The impact of residence time on non‐native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land‐use types. The unpredictability of future impacts, implied by the slow spread of non‐native species, strengthens the call for stronger regulations on the exchange of non‐native species to reduce the long‐lasting invasion debt looming on ecosystems' future.